(untitled) (Journal of Applied Learning and Teaching, 2020)
Introduction: Several studies recommend a Multisectoral approach to promote positive sexual behaviors among young people. Minimal literature exists on influence of parent-teacher interaction on sexual behaviors of young people. Objective: To examine the influence of parent-teacher interaction on initiation of sexual practices among teenagers in Kawuku S.S Mukono District, Uganda Methods: Qualitative phenomenological design was used. The respondents were; 12 parents who had children in the school, 6 teachers who had been in the school for at least 3years and 18 teenagers 13-19 years of age from the school. In-depth structured interview and Focus Group Discussions (FGDs) were held. It looked at whether parents interacted with teachers on matters regarding their children’s sexual behaviors, the frequency `and content discussed and how this impacted on the sexual decisions and practices of young people concerned. Results: Interaction facilitated flow of protective information and guidance that led to delayed sexual debut and improving the sexual behaviors among the teenagers. Most of the teenagers whose parents were in close interaction with their teachers attributed their present sexual behaviors to raised consciousness and fear created by continuous monitoring and communication from either party. Number of barriers hindered effectiveness of parent-teacher interaction. These included lack of appropriate sexual information among parents, parents’ fear to discuss strong sexual- experiences with young people, poor parenting, limited confidentiality among teachers and so on. Conclusion: When parents have right sexual information and interact well with teachers on matters regarding sexual behaviours of their children, positive sexual behaviours and delayed sexual debut among teenagers is facilitated.